Sistem Informasi E-Booking Berbasis Website pada PT. SKI Land Development - Dewi, Komang Ratih Sucitya (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
PT. SKI Land Development is a consulting service company engaged in property buying and selling consultancy services and has a standardized developer listing to avoid problematic property purchases in the future. The projects of PT. SKI Land Development are spread throughout Bali. the product marketing stage, product information, house booking, and company schedules are still done offline.. The solution provided to PT. SKI Land Development is to create a